Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00330-011-2277-1
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of volume and densitometric measures of emphysema on repeat computed tomography with an interval of 1 week

Abstract: • Good breath-hold reproducibility is achievable between multiple CT examinations. • Reproducibility of densitometric measures may be improved by statistical volume correction. • Volume correction may result in decreased signal. • Densitometric reproducibility may also be improved by achieving good breath-hold reproduction. • Careful consideration of signal and noise is necessary in reproducibility assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The lung tissue was then further divided by adding the pixels within pre-defined CT attenuation limits in volumes and was then expressed as percentage of the entire lung volume [4,17]. Volumes in the range -300 to -750 HU were considered to represent pixels including tissue such as small bronchi, vessels and borders with denser structures (partial volume effect) and were analysed separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lung tissue was then further divided by adding the pixels within pre-defined CT attenuation limits in volumes and was then expressed as percentage of the entire lung volume [4,17]. Volumes in the range -300 to -750 HU were considered to represent pixels including tissue such as small bronchi, vessels and borders with denser structures (partial volume effect) and were analysed separately.…”
Section: Methodsmentioning
confidence: 99%
“…Computer tomography (CT) imaging of the lung can non-invasively detect and quantify lung abnormalities [4-7]. Early changes in airways and lung parenchyma may be recognized in smoking individuals with normal pulmonary function before any signs of lung function impairment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative CT techniques for emphysema scoring are objective and therefore preferable to visual analysis (7). Recent studies have also demonstrated that CT lobar volumetry has good inter scan reproducibility (8)(9)(10). Among the different sources of variability of CT lung volumetry and emphysema scoring, those depending on the method used for lobar segmentation have received little attention (5).…”
mentioning
confidence: 99%
“…However, to be able to detect disease progression or effects of therapy, variation between examinations should be within acceptable limits as disease progression is defined as an increase above the upper limit of such variation. The variation with the limits of agreement for repeat CT studies in emphysema is known [8, 9]; however, to our knowledge no information is available on the variation of CT air trapping quantification. Therefore, the objective of this study was to determine the variation in two commonly used quantitative CT air trapping measures in current and former heavy smokers.…”
Section: Introductionmentioning
confidence: 99%